Prevalence and trajectories of neuropsychological post-COVID-19 symptoms in initially hospitalized patients - Simona Klinkhammer; Annelien A. Duits; Janneke Horn; Arjen J.C. Slooter; Esmée Verwijk; Susanne van Santen; Johanna M.A. Visser-Meily; Caroline van Heugten (Medical Journals Sweden, 2024)
Objective: To investigate the prevalence and trajectories of post-COVID-19 neuropsychological symptoms. Design: Prospective longitudinal multicentre cohort study. Subjects: A total of 205 patients initially hospitalized with SARS-CoV-2 (COVID-19). Methods: Validated questionnaires were administered at 9 months (T1) and 15 months (T2) post-hospital discharge to assess fatigue, cognitive complaints, insomnia, anxiety, depression, and post-traumatic stress symptoms. Results: Analyses included 184 out of 205 patients. Approximately 50% experienced high cognitive complaints at T1 and T2, while severe fatigue affected 52.5% at T1 and 55.6% at T2. Clinically relevant insomnia scores were observed in 25% of patients at both time-points. Clinically relevant anxiety scores were present in 18.3% at T1 and 16.7% at T2, depression in 15.0% at T1 and 18.9% at T2, and PTSD in 12.4% at T1 and 11.8% at T2. Most symptoms remained stable, with 59.2% of patients experiencing at least 1 persistent symptom. In addition, 31.5% of patients developed delayed-onset symptoms. Conclusion: Post-COVID-19 cognitive complaints and fatigue are highly prevalent and often persist. A subgroup develops delayed symptoms. Emotional distress is limited. Screening can help identify most patients experiencing long-term problems. Future research should determine risk factors for persistent and delayed onset symptoms.